Modelling the social media content marketing (SMCM) criteria on content marketing experience (CMX) and behavioral intention towards Muslimah fashion advertisement / Nur Syakirah Ahmad - Ahmad, Nur Syakirah (2023)
In this new era of digital marketing, the social media becoming a crucial business tool among the business firms. Most of the business practitioners especially in Muslimah fashion industry start to realise the importance of content marketing towards their business development. According to past research, many business firms have challenges to provide an effective content marketing criteria that meet the customer’s needs especially in producing high quality content for photo, video, and website. Thus, it is crucial to find what are the main criteria of content marketing that can help the firms to strengthen their business. In addition, there is limited research methodology approaches that have been used to define good criteria of content marketing specifically on photo, video, and website. Previous studies also found that business discourse recommends customers to seek satisfying experiences on social media particularly on their emotion towards content marketing. However, by providing good criteria of content marketing, it will affect the emotion and behavioural intention among the social media users in terms of virality and brand loyalty. There are still not much specific criteria for social media content marketing that can be applied by the business practitioners, making it difficult to provide high quality of content marketing for online customers. The research aimed to conceptualise and operationalize Social Media Content Marketing (SMCM); video quality, photo quality and website quality and Content Marketing Experience (CMX) scales to determine what are the criteria for an effective content marketing and emotions that triggered among Muslims urban female millennial towards Muslimah fashion advertisement. Then, this study also aims to investigate their behavioural intentions. SMCM integrates video quality, photo quality, website quality, CMX, virality and brand loyalty. By using the judgment sampling method, the data was collected with Muslims urban female Millennials who live in Shah Alam, Selangor. There were 300 respondents involved in this study. There are five hypotheses that have been investigated in this study. SOR and content marketing theories were integrated in this study to develop the research framework. The data were analysed through SPSS and SEM AMOS to explore and confirm all the factors whereas eye-tracking was used in this study to support the SMCM criteria findings. The results achieved and an acceptable model fit value and showed a significant relationship between video quality, photo quality and website quality and CMX. Meanwhile, CMX significantly affect behavioural intention of virality and brand loyalty. The result of eye-tracking found that the elements of the product, information, human and environment in video and photo have high visual attention from respondents. As a result, this study concludes that, SMCM can be divided into two elements which is implicit and explicit criteria. Both criteria can give positive impact towards Muslims urban female millennials’ emotions as well as their behavioural intention of virality. Thus, based on these findings it will help the business practitioners to produce high quality of SMCM especially for Muslimah fashion advertisement. Meanwhile, CMX potential allows them to have a stronger impact on business performance specifically on customer engagement, and brand awareness. Future research can investigate the SMCM criteria for other group of customers with different types of product advertisements.